A rare occurrence of plasma cell myeloma with biclonal gammopathy - Mardziah M,; Nurasyikin Y,; Rafeah T,; Dian N,; Suria Abdul Aziz, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Plasma cell myeloma is known to cause expansion of a single clone of immunoglobulin (Ig) which results in the secretion of a unique homogeneous monoclonal protein (M component). However, there are cases which reported that it can also cause production of two different clones of these monoclonal M proteins. Although it is relatively very rare as the prevalence is only 2% of all plasma cell myeloma cases, the clinical features are said to be similar to monoclonal gammopathy. It is suggested that these biclonal gammopathy results from either one monoclonal cell clone in monoclonal gammopathy or two different monoclonal cell clones. Whichever the mechanism of the disease be, the response to treatment seems to be similar as compared to the monoclonal cases although some reports shows chemoresistant. Here, we report a rare case of plasma cell myeloma with IgG (lambda) and IgA (lambda) type of biclonal gammopathy, the clinical presentation, the haematological and biochemical markers as well as the response to the treatment.